2008
DOI: 10.1002/hed.20905
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of maxillofacial brown tumors after parathyroidectomy in primary hyperparathyroidism

Abstract: After successful parathyroid surgery, the bony lesions tended to regress spontaneously, either partially or completely. However, if the lesion is disfiguring or symptomatic, surgical excision may be indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
52
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 21 publications
2
52
0
2
Order By: Relevance
“…Our patient was much younger than average, which supports the findings of Al-Gahtany et al, who reviewed 16 cases involving brown tumors of the skull base, and revealed that the mean age of the patients was 32 years, and that 75% of them were women [2]. Resendiz-Colosia et al have reported a series of 22 cases of maxillofacial brown tumor, showing that 91% of them were women [6]. A possible explanation is that young women have greater susceptibility for PTH and a predisposition to brown tumors.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our patient was much younger than average, which supports the findings of Al-Gahtany et al, who reviewed 16 cases involving brown tumors of the skull base, and revealed that the mean age of the patients was 32 years, and that 75% of them were women [2]. Resendiz-Colosia et al have reported a series of 22 cases of maxillofacial brown tumor, showing that 91% of them were women [6]. A possible explanation is that young women have greater susceptibility for PTH and a predisposition to brown tumors.…”
Section: Discussionsupporting
confidence: 93%
“…Screening for hypercalcemia can lead to early treatment of hyperparathyroidism and prevent the development of advanced bony complications. The combination of vitamin D deficiency and primary hyperparathyroidism predisposes patients to develop the classic skeletal changes of primary hyperparathyroidism [6,8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large lesions may resolve very slowly or may regress with resultant asymmetry on the face. In this case, the curettage, surgical excision or resection of the remaining brown tumour after the resolution of HPT may be planned to restore function and to reduce the risk of fracture (Reséndi-Colosia et al, 2008). Daniels (2004) presented a case of a brown tumour of primary hyperparathyroidism in the mandible treated with curettage of the lesion.…”
Section: Discussionmentioning
confidence: 98%
“…In this case, the inability of the patient to breathe through the left nostril and epiphora was caused by the presence of large tumour compressing the left nasal passage and the nasolacrimal duct (Daniels, 2004). According to Reséndi-Colosia et al (2008) correct diagnosis alone can avoid an unnecessary bone resection. However, if the patient wants a quick resolution, or if bony lesion promotes facial deformation, or if the lesion failed to regress, surgical resection of the brown tumour should be considered.…”
Section: Discussionmentioning
confidence: 98%